The impact of the Agency's second conflict in the dividend policy and its impacts on the quality of profits: Applied to a sample of companies listed on the Iraq Stock Exchange - Talal Ibrahim, Saher; Muhsein Hameed, Anmar; Najem. Aubdullah AlMashhadani, Bushra (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to study the effect of conflict of interest between the main shareholders and small shareholders in the dividend policy and its impact on the quality of the declared profits, as the impact of the agency's second conflict is reflected in the economic decisions that are implemented within the company, including the decision to determine the amounts that will be distributed to shareholders from the total Realized profits and amounts. For the purpose of achieving the research goal, the multiple linear regression model was used to measure the impact of the conflict of interests of major shareholders and small shareholders in the dividend policy and its reflection on the quality of the declared profits, which was measured through the modified Jones model to test the quality of the profits of companies in the research sample, and the research has concluded that Profits declared for the companies of the research sample (23) companies listed on the Iraq Stock Exchange for the period from 2016 to 2018 are not characterized by quality and there is a statistically significant relationship between the conflicts of interests of major shareholders and small shareholders and the policy of distributions as well as there are on Statistical significance between the agency's second conflict, and dividend policies and advertised profit quality.